FERRY ZEIN MAESTRO MUSIC DAN PENCIPTA LAGU MINANG 1976-2011 - Destariza, Rina; Husnita, Liza; Ersi, Livia (Pendidikan Sejarah, 2014)
Ferry Zein as Maestro Music and minangâs songwriter (1976-2011). History Education Program. STKIP PGRI West Sumatera.Padang. 2014. This thesis discusses about the journey of Ferry Zein as Maestro Music and minangâs songwriter (1976-2011). To facilitate this research, the problem can be formulated as follows: (1) what is the background of Ferry Zeinâs life. (2) How does Ferry Zein begin his carrier as minangâs songwriter. (3) What is the popular song of Ferry zein and how is society opinion about his work. The primary purpose of this research are (1) to know how the background of Ferry Zeinâs life. (2) To describes how the journey of Ferry Zein as minangâs songwriter . (3) To know popular song of Ferry Zein and society opinion about his creation. Types of this research is thematic biography, it means writing biography Ferry Zein limited role as a minangâs songwriter. This research use historical method. The method consists of the following four stages namely Heuristic, Doing Criticism Sources, Interpretation, Historiography. The method used in this study is the historical method. The method consists of the following four stages: (1 ) Heuristic is a collect the data , looking for the source and conclude to library study and interviews.(2) Criticism source, in order to obtain the facts of history . ( 3 ) Interpretation, the obtained data analyzed and interpreted with connecting and comparing the observed facts so the fact that ready to be served . (4 ) Historiography,Â writing in the form of scientific papers after collect the data and facts that really accurate and valid then write in the form of a thesis. This study describes the results : ( 1 ) The background of Ferry Zeinâs life from simple family ( 2 ) the journey of Ferry Zein as minangâs songwriter give existence in music life which popularize old singer and new singer, and he gets many awards, one of them is reward from West Sumatera governor Irwan Prayitno as one of best figure west Sumatera in 2011.(3) Ferrys song easily to remember, good to sound so popular in teenagers also older.